1994
DOI: 10.1161/01.cir.90.6.2956
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose, beta-particle emission from 'stent' wire results in complete, localized inhibition of smooth muscle cell proliferation.

Abstract: BACKGROUND Restenosis after catheter-based revascularization has been demonstrated to be primarily caused by medial and/or intimal smooth muscle cell (SMC) proliferation. The objective of this study was investigate the ability of local emission of beta-particles from a 32P-impregnated titanium "stent" wire source to inhibit vascular SMC and endothelial cell proliferation in cell culture and to determine the dose-response characteristics of this inhibition. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
5

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(39 citation statements)
references
References 43 publications
0
34
0
5
Order By: Relevance
“…Coupling the radiation delivery to the stent itself makes radiation delivery more efficient, obviating the need for a separate radiation delivery step. Several radioactive stent systems have been developed including ion-implantation of phosphorous-32 ( 32 P) 11 and activation of a stainless steel stent in a cyclotron producing a spectrum of radioisotopes. 12 Most clinical investigation has been undertaken with the 32 P ␤-emitting stent.…”
Section: Radioactive Stentsmentioning
confidence: 99%
“…Coupling the radiation delivery to the stent itself makes radiation delivery more efficient, obviating the need for a separate radiation delivery step. Several radioactive stent systems have been developed including ion-implantation of phosphorous-32 ( 32 P) 11 and activation of a stainless steel stent in a cyclotron producing a spectrum of radioisotopes. 12 Most clinical investigation has been undertaken with the 32 P ␤-emitting stent.…”
Section: Radioactive Stentsmentioning
confidence: 99%
“…It is also believed that radioactive stents can act by culling the smooth muscle cell population as these cells pass through the "electron fence" at the plane of the stent wires. 115 Hehrlein and colleagues 116,117 were the first to describe the use of radioactive stents, which they implanted in nondiseased rabbit iliac arteries. The stainless steel stents were made radioactive by ion bombardment in a cyclotron and emitted both ␥-and ␤-radiation from the radionuclides 55,56,57 Co, 52 Mg, and 55 Fe.…”
Section: Radioactive Stentsmentioning
confidence: 99%
“…However, stent thrombosis is not always seen in animal models of catheter based brachytherapy. Fischell and co-workers 67) postulated delayed endothelialization predisposing the thrombus formation. Hehrlein and co-workers have shown that the reendothelialization after low-dose radioactive stent implantation was delayed, with the rate of stent endothelialization being dose-dependent.…”
Section: Radiobiology Of the Arterial Wallmentioning
confidence: 99%
“…88) A similar technique was independently developed and tested by Fis-chell and co-workers. 67) 31 P was ion-implanted beneath the outer surface of the titanium wire of stents, which were exposed for several hours to a flux of slow neutrons to produce a pure beta-emitter. It offers the advantages of no associated gamma radiation, a short half-life (14.3 days), and limited range of the beta particles in tissue (3 to 4 mm).…”
Section: Radioactive Stents In Animal Studiesmentioning
confidence: 99%